European Consortium for Lipodystrophies consensus definition and classification framework for monogenic lipodystrophy - Robert K. Semple; Martin Wabitsch; Baris Akinci; Saif Alyaarubi; Marjoleine F. Broekema; Rebecca J. Brown; Giovanni Ceccarini; Carolina Cecchetti; Solaf M. Elsayed; Antía Fernández‐Pombo; Alessandra Gambineri; Ingrid M. Jazet; et al. (Journal of Internal Medicine, 2026)
Abstract Lipodystrophy comprises a heterogeneous group of disorders characterized by reduced adipose tissue often associated with severe metabolic complications. Lipodystrophy may be genetic, acquired, or secondary to medical therapies initiated for other conditions. Despite major advances in understanding adipose tissue biology and in human genetic technologies, diagnosis of lipodystrophy is still commonly delayed or missed. Conversely, increasing use of next‐generation sequencing has led to proliferation of proposed new genetic causes of lipodystrophy with variable supporting evidence. To address these challenges, an international expert working group from the European Consortium for Lipodystrophies first developed a consensus definition of lipodystrophy as deficient development and/or inadequate maintenance of adipose tissue not attributable to nutritional deprivation or a systemic catabolic state. Anatomical adipose deficiency alone is generally insufficient for diagnosis, with evidence of adipose tissue dysfunction or pathology also usually required. Building on this definition, a framework for evaluating candidate monogenic lipodystrophy syndromes is suggested, based on the strength of human phenotypic, genetic, and biological evidence. Primacy was assigned to direct evidence from affected individuals, with genetic and biological evidence considered supportive but not determinative. This approach accommodates both the variable penetrance and expressivity characteristic of many lipodystrophy syndromes and potential discrepancies between human observations and experimental models. Although the proposed definition is applicable across all forms of lipodystrophy, the classification system described here is restricted to monogenic disorders. Together, these tools aim to improve clinical recognition, promote diagnostic consistency, and provide a robust and adaptable framework for evaluating emerging gene–disease associations in lipodystrophy.